The influence of technical infrastructure on the roundabout areas development = Wpływ infrastruktury technicznej na formę zagospodarowania rond - Kostecki, Jakub; Greinert, Andrzej; Owoc, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the analysis of roundabouts design aspects including the location of underground and overground infrastructure. Authors also undertake an attempt to assess the existing situation with planning conditions. Many differences depended on the roundabout size, location, surroundings, natural conditions, landform technology used were noted.
Keywords: roundabout; land development; landform; hard infrastructure; rondo; zagospodarowanie przyrodnicze; kształtowanie terenu; infrastruktura techniczna